2019
DOI: 10.1167/iovs.19-27524
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Stargardt Disease Due to Mild, Deep-Intronic ABCA4 Alleles

Abstract: PURPOSE. To investigate the role of two deep-intronic ABCA4 variants, that showed a mild splice defect in vitro and can occur on the same allele as the low penetrant c.5603A>T, in Stargardt disease (STGD1). METHODS. Ophthalmic data were assessed of 18 STGD1 patients who harbored c.769-784C>T or c.4253þ43G>A in combination with a severe ABCA4 variant. Subjects carrying c.[769-784C>T; 5603A>T] were clinically compared with a STGD1 cohort previously published carrying c.5603A>T noncomplex. We calculated the penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Although 76% of registrations related to Stargardt disease were in the working-age group, we found 10% were registered up to the age of 15 and 14% were registered at 65years or older, with a bimodal peak. This is consistent with the extreme variability in phenotype ranging from severe childhood-onset to late-onset disease, which has a median age of onset in the mid-50 with up to 11% of these individuals eligible for blindness registration (23,28). Another retrospective crosssectional study of 361 patients with Stargardt disease found 59% met the criteria for blindness registration and the median time to develop this degree of visual impairment varied from 22 to 29 years depending on the BCVA at the patient's initial visit (29).…”
Section: Discussionsupporting
confidence: 82%
“…Although 76% of registrations related to Stargardt disease were in the working-age group, we found 10% were registered up to the age of 15 and 14% were registered at 65years or older, with a bimodal peak. This is consistent with the extreme variability in phenotype ranging from severe childhood-onset to late-onset disease, which has a median age of onset in the mid-50 with up to 11% of these individuals eligible for blindness registration (23,28). Another retrospective crosssectional study of 361 patients with Stargardt disease found 59% met the criteria for blindness registration and the median time to develop this degree of visual impairment varied from 22 to 29 years depending on the BCVA at the patient's initial visit (29).…”
Section: Discussionsupporting
confidence: 82%
“…32 It should also be noted, however, that evidence is emerging that some variants that were long considered pathogenic or benign by themselves, such as c.2588G>C; p.[G863A,G863del] and c.5603A>T; p.(N1868I), are fully penetrant only when in combination on the same allele. The same is true for the cis configuration of p.(N1868I) with a recently identified intronic mutation, c.769-784C>T. 9,33,34 In addition, modifier variants, either within or outside of ABCA4, as well as environmental factors will likely play a role in determining disease outcome. 9 Thus, care is warranted when attributing a severity score to individual alleles.…”
Section: Discussionmentioning
confidence: 91%
“…A step further in genetic diagnosis has been attained when deep-intronic variants that alter the splicing pattern have been identified, as is the case in Stargardt disease, a macular disorder with a very well defined clinical phenotype and a major causative gene, ABCA4. In fact, the introduction of the whole ABCA4 locus in the target NGS panels clearly helps to increase the genetic yield in Stargardt disease patients [16,17].…”
Section: Discussionmentioning
confidence: 99%